2015
DOI: 10.3906/sag-1401-127
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro and in vivo investigation of the cytotoxic effects of caffeic acid (3,4-dihydroxycinnamic acid) phenethyl ester and bortezomib in multiple myeloma cells

Abstract: IntroductionMultiple myeloma (MM) is a hematologic cancer characterized by uncontrolled monoclonal plasma cell proliferation (1). MM is currently an incurable B-cell malignancy that accounts for nearly 10% of human hematopoietic cancers and 1% of all human cancers (2). Presently, the 2 most effective treatment choices for patients with MM are tandem high-dose chemotherapy followed by autologous stem cell infusion, or allogeneic hematopoietic stem cell transplantation after myeloablative therapy or reduced-inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…We studied how NIH-3T3 fibroblast cells will react to the CAFeB nanomedicine and we found out that it created a slight cytotoxic effect, but due to the inherent lower levels of mitochondrial ROS on normal cells, oxidative stress did not reach apoptotic and necrotic threshold, thus exhibiting a lower cytotoxic effect compared with malignant cells (CT26) ( Figures S4-S6 of Supplementary Materials). Lastly, this study further validated the combinatory effects of CA and BTZ reported by Altayli et al [22], where comprehensive in vivo and in vitro studies were made using a multiple myeloma cell line. However, our nanoparticle formulation can improve the dosing and administration of both CA and BTZ by combining them into a single nanomedicine platform, potentially improving the pharmacokinetic behavior of both molecules once used in vivo.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…We studied how NIH-3T3 fibroblast cells will react to the CAFeB nanomedicine and we found out that it created a slight cytotoxic effect, but due to the inherent lower levels of mitochondrial ROS on normal cells, oxidative stress did not reach apoptotic and necrotic threshold, thus exhibiting a lower cytotoxic effect compared with malignant cells (CT26) ( Figures S4-S6 of Supplementary Materials). Lastly, this study further validated the combinatory effects of CA and BTZ reported by Altayli et al [22], where comprehensive in vivo and in vitro studies were made using a multiple myeloma cell line. However, our nanoparticle formulation can improve the dosing and administration of both CA and BTZ by combining them into a single nanomedicine platform, potentially improving the pharmacokinetic behavior of both molecules once used in vivo.…”
Section: Discussionsupporting
confidence: 80%
“…BTZ is a synthetic anticancer drug that inhibits NF-κB by binding to the 26S proteasome of cancer cells with high affinity and specificity, thereby resulting in reduced protein degradation tagging and apoptosis [16][17][18][19]. BTZ can complement the use of caffeic acid by virtue of inhibition of the survival mechanism of the cell, while CA creates intracellular DNA and protein damage via the induction of reactive oxygen species (ROS) [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…It exerts anti-inflammatory, anti-atherosclerotic, and anti-tumor pharmacological effects [ 33 ]. In addition, caffeic acid, an active component of honeybee propolis, has cytotoxic, apoptosis, and anti-proliferation effects [ 34 ].…”
Section: Flavonoids and Non-flavonoid Polyphenols In MM Therapymentioning
confidence: 99%
“…These include anti-inflammatory and antioxidative actions ( 81 , 82 ), antidiabetic ( 83 ), and hepatoprotective ( 84 ), and antineoplastic ( 85 , 86 ). Caffeic acid (3,4-dihydroxycinnamic acid) phenethyl ester (CAPE) is reported cytotoxic and anti-proliferative actions on RPMI 8226, H929, U266 and ARH77 cell lines, and also synergises with bortezomib in growth inhibition and reduction of NF-kB binding activity and IL6 levels ( 87 ). In preclinical studies, caffeic acids and its analogues have also been reported to downregulate specificity protein 1 and IKZF1-IRF4-MYC axis in myeloma cells including cell lines resistant to immunomodulatory drugs lenalidomide and pomalidomide ( 88 ).…”
Section: Flavonoidsmentioning
confidence: 99%